Effect of golimumab on endothelial vasomotor function and arterial stiffness in ankylosing spondylitis - L. A. Knyazeva; N. Damjanov; L. I. Knyazeva; N. S. Meshcherina; I. I. Goryainov; M. A. Stepchenko; Ya. I. Bobyntsev; O. S. Rudakov (Научно-практическая ревматология, 2019)
Objective: to evaluate the effect of golimumab (GLM) on endothelial vasomotor function and arterial stiffness in patients with ankylosing spondylitis (AS).Subjects and methods. A total of 42 patients with advanced-stage AS, who were older than 18 years and met the 1984 modified New York criteria with a disease duration of ≤5 years, were examined. The investigators visualized carotid arteries to determine local vascular wall stiffness, studied regional arterial stiffness to assess a pulse wave contour analysis, and a reactive hyperemia test before and after 104-week therapy.Results and discussion. RA patients without cardiovascular comorbidity were found to have signs of subclinical great artery involvement accompanied by endothelial vasoregulatory dysfunction in both the small resistance and large muscular arteries; by increases in common carotid artery (CCA) intima-media thickness (IMT) and stiffness index (SI); by rises in peripheral augmentation index (AIp), SI and reflection index (RI), the intensity of a change in which correlated with disease duration and activity assessed by ASDAS; as well as with the modified Schober test value, cervical rotation, and tragus-to-wall distance. In addition to a decrease in the Ankylosing Spondylitis Disease Activity Score (ASDAS), GML treatment in patients with AS caused a statistically significant increase in the amplitude occlusion index to the control values and a rise in the phase shift between the channels by an average of 2 times (p<0.01) as compared to the baseline values; a decrease in CCA IMT by an average by 20% (p=0.01) and in the local stiffness of the (carotid) vascular bed by 31% (p=0.01). The pulse wave contour analysis after 104-week GLM therapy revealed that AIp, SI and RI decreased by an average of 5 (р<0.001), 1.3 (р<0.01), and 2 (p<0.05) times, respectively, with the remaining statistically significant differences from the control values.Conclusion. In addition to the effectively reduced inflammatory activity, GLM therapy in patients with AS provides restoration of endothelial function in both the small resistance vessels (an increase in the amplitude occlusion index) and the large muscular arteries (a rise in the phase shift between the channels) and also has a vasoprotective effect on the wall of large elastic vessels (reductions in CCA IMT, SI, AIp, and SI) and small muscular arteries (a decrease in RI).